Resistance of Laminated Veneer Lumber (LVL) produced from rubberwood, radiata pine and larch against subterranean termites and white rot fungi - Md Tahir, Paridah; Abdul Halip, Juliana; Lee, Seng Hua (Lupine Publishers, 2018)
Laminated veneer lumbers (LVLs) were fabricated using rubber wood, radiate pine and larch wood. Solid rubber wood was used to serve as control for comparison purpose. All of the wood samples were exposed to subterranean termites and white rot fungi for durability evaluation. The results showed that rubber wood LVL had the highest resistance against both deterioration agents in comparison to control, confirming that the resistance of non-durable wood species could be improved by converting them into LVL.